Board Gender Diversity and Corporate Social Responsibility: Evidence from Listed Healthcare Firms in Nigeria - Akpan, Dorathy Christopher; Otung, Affiong Ukana; Nsentip , Ese Bassey (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Despite growing global attention on gender diversity in corporate governance, the extent to which board gender equality influenced corporate social responsibility remained underexplored, particularly in emerging markets with weak institutional frameworks. This study examined the impact of board gender diversity on corporate social responsibility performance among listed healthcare firms in Nigeria from 2013 to 2023. Corporate social responsibility performance was the dependent variable while board gender diversity was the independent variable, with firm-specific controls including market capitalization, firm size, leverage, profitability and financial distress. The research design adopted was ex post facto, secondary data were utilized, and the sample comprised five listed healthcare firms, and robust regression analysis was employed to analyze the study. The findings revealed a significant positive relationship between board gender diversity and corporate social responsibility performance, reinforcing stakeholder and resource dependence theories, which suggest that diverse leadership enhances ethical decision-making and sustainability orientation. These results offer compelling policy implications, advocating for stronger corporate governance regulations that mandate gender diversity in boardrooms. The study also highlighted the need for firms to view gender diversity not merely as a compliance requirement but as a strategic advantage in fostering long-term sustainability.